Boiler dynamics and control in nuclear power stations 2 proceedings of the second international conference held in Bournemouth, 23-25 October, 1979 - Harding, Bonny (British Nuclear Energy Society, 1980)
Papers are grouped into headings: 'Transients', 'Model Validation', 'Hydrodynamic Stability', 'Modelling and Computational Techniques', 'Control Systems', 'Codes', 'Data and Steady State' and 'Commissioning'.